KELIMPAHAN DAN PERTUMBUHAN IKAN GULAMAH (Johnius trachycephalus) DI PERAIRAN ESTUARISUAKA MARGASATWA KARANG GADING KABUPATEN DELI SERDANG - Dean Amunike; Desrita Desrita (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2018)
The aim of this research is to determine the abundance and growth of Gulamah fish (Johnius trachycephalus) in estuaries of Suaka Margasatwa Karang Gading of Deli Serdang Regency. Sampling was carried out at 3 research stations and for 60 days starting from March to May 2018. Fish was caught with fishing gear mini trawl ring. Water quality measurements was carried out in situ. Overall, the condition of the estuaries of Suaka Margasatwa Karang Gading of Deli Serdang Regency was still above the water quality standard. The highest abundance occurs in station II, because station II was composed of natural ecosystems, namely mangroves. The value of the length and weight of Gulamah fish at each station was allometric negative with a value of b <3 and the condition factor value of each station shows a value of FK> 1, which indicates that the condition of Gulamah Fish in estuaries of Suaka Margasatwa Karang Gading of Deli Serdang Regency can morphologically said to have a good fortune.Keywords: Abundance, Aquatic Conditions, Growth, Gulamah Fish